2020
DOI: 10.1007/s10068-020-00824-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea polyphenols on physicochemical and antioxidative properties of whey protein coating

Abstract: Effects of tea polyphenols (TP) incorporation on physicochemical and antioxidative properties of whey protein isolate (WPI) coating were studied. Two WPI coating solutions were prepared by heating WPI solutions (pH 8, 90 °C) for 30 min and then TP was incorporated. TP addition could increase the negative zeta potential of 5% solution. The surface hydrophobicity index of both solutions was increased and intrinsic fluorescence intensity decreased greatly after addition of TP. 2,2-Diphenyl-1picrylhydrazyl (DPPH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…To solve these problems, various studies have been conducted to optimize the extraction process, combine other antimicrobial substances, apply active packaging, and encapsulate antibacterial substances to improve their utilization [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…To solve these problems, various studies have been conducted to optimize the extraction process, combine other antimicrobial substances, apply active packaging, and encapsulate antibacterial substances to improve their utilization [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3, hydrophobic force was formed mainly at hydrophobic amino acids (gliadin at PRO and LYS, LMW‐glutenin at LEU, HWM‐glutenin at PRO). It has been reported that the aromatic group of phenols and hydrophobic amino acids of protein lead to the formation of hydrophobic force between TP and gluten (Ming et al., 2020). In summary, hydrophilic hydroxyl groups and hydrophobic aromatic groups of TP facilitated the interactions with gluten by forming hydrogen bonds and hydrophobic forces, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence quenching can be segmented into static quenching and dynamic quenching [ 35 ]. Whey protein can emit fluorescence at a wavelength of 280 nm because it contains tyrosine and tryptophan [ 36 ]. Different amounts of PNS fluorescence quenching were investigated, as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%